2015
DOI: 10.3945/ajcn.114.103655
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D insufficiency is associated with increased risk of first-trimester miscarriage in the Odense Child Cohort

Abstract: We found an association between 25(OH)D and first-trimester miscarriages, suggesting vitamin D as a modifiable risk factor for miscarriage. To test this hypothesis, randomized controlled trials should investigate the possible effect of vitamin D supplementation to increase 25(OH)D concentrations in early pregnancy, or before conception, to decrease risk of miscarriage. This trial was registered at clinicaltrials.gov as NCT02434900.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
64
1
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(71 citation statements)
references
References 41 publications
1
64
1
5
Order By: Relevance
“…This corresponds with the findings from previous largescale studies on 25(OH)D concentrations in pregnant women in Nordic countries. The Norwegian Mother and Child Cohort Study found a 25(OH)D mean level of 74 nmol/l in midpregnancy [30] whereas the Danish Odense Child Cohort study revealed a median mid-pregnancy level of 66 nmol/l [31]. The use of cod-liver oil by pregnant women in Norway [32] could potentially contribute to the observed relatively higher 25(OH)D levels.…”
Section: Discussionmentioning
confidence: 91%
“…This corresponds with the findings from previous largescale studies on 25(OH)D concentrations in pregnant women in Nordic countries. The Norwegian Mother and Child Cohort Study found a 25(OH)D mean level of 74 nmol/l in midpregnancy [30] whereas the Danish Odense Child Cohort study revealed a median mid-pregnancy level of 66 nmol/l [31]. The use of cod-liver oil by pregnant women in Norway [32] could potentially contribute to the observed relatively higher 25(OH)D levels.…”
Section: Discussionmentioning
confidence: 91%
“…Zhang et al (2017) in a systematic review and meta-analysis, which included 5 cohort studies, [55][56][57][58][59] concluded that an extremely low 25(OH)D level (<20 ng/mL) was significantly associated with an increased risk of SA in the first trimester. Zhang et al (2017) in a systematic review and meta-analysis, which included 5 cohort studies, [55][56][57][58][59] concluded that an extremely low 25(OH)D level (<20 ng/mL) was significantly associated with an increased risk of SA in the first trimester.…”
Section: Introductionmentioning
confidence: 99%
“…Two authors (ZH and XJ) independently extracted original data from the selected papers using the developed data abstraction form, and a third author (LX) made a decision when disagreements occurred. Because data for two cohort studies were inaccessible, we tried to contact the authors of these studies via email to acquire the data for calculating the RRs. Andersen et al .…”
Section: Methodsmentioning
confidence: 99%